First detection of Blastocystis sp. in migratory whooper swans (Cygnus cygnus) in China - Kaihui Zhang; Ziyang Qin; Huikai Qin; Yinlin Wang; Luyang Wang; Yin Fu; Changjiang Hou; Chenxiao Ji; Yuan Yuan; Longxian Zhang (One Health, 2023)
Blastocystis is a usual intestinal protist that always found in humans and various animals. Currently, the prevalence of Blastocystis in the migratory whooper swan (Cygnus cygnus) is unknown. In our research, we aimed to determine the occurrence, prevalence, subtype distribution and dynamic transmission mechanisms of Blastocystis in the migratory whooper swan in China. We also assessed the zoonotic potential of Blastocystis isolates, as well as possible routes of transmission and impact of this organism on One Health perspective. Fecal samples (n = 770) were collected from whooper swans inhabiting the Sanmenxia Swan Lake National Urban Wetland Park, China. The overall prevalence of Blastocystis was 11.6% (89/770). We identified 9 subtypes of Blastocystis sp., including 5 zoonotic subtypes [ST1 (Cakir et al., 2019 (8)), ST4 (Selma and Karanis, 2011 (4)), ST5 (Stensvold et al., 2009 (1)), ST6 (Fare et al., 2019 (5)) and ST7(58)] and 3 host-specific subtypes [ST10 (Zhao et al., 2018 (7)), ST14 (Tan et al., 2010 (2)), ST23 (Wang et al., 2018 (3)), and ST25 (Stensvold et al., 2009 (1))]. Subtypes ST4, ST5, ST6, ST10, ST14, ST23, and ST25 were first identified in the whooper swan. Among these subtypes, ST23 and ST25 were identified in birds for the first time, indicating that these subtypes are expanding their host range. So far, this is the first research reporting on the prevalence and subtypes distribution of Blastocystis in the migratory whooper swan in China. The findings obtained in this study will provide new insights into the genetic diversity and transmission routes of Blastocystis, and the possible public health concerns posed by this organism.